2009
DOI: 10.1007/s12088-009-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promoting potential of the fungus Discosia sp. FIHB 571 from tea rhizosphere tested on chickpea, maize and pea

Abstract: The ITS region sequence of a phosphate-solubilizing fungus isolated from the rhizosphere of tea growing in Kangra valley of Himachal Pradesh showed 96% identity with Discosia sp. strain HKUCC 6626 ITS 1, 5.8S rRNA gene and ITS 2 complete sequence, and 28S rRNA gene partial sequence. The fungus exhibited the multiple plant growth promoting attributes of solubilization of inorganic phosphate substrates, production of phytase and siderophores, and biosynthesis of indole acetic acid (IAA)-like auxins. The fungal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Change of blue color of the medium surrounding the bacterial growth to fluorescent yellow indicated the production of siderophore. Bacillus subtilis was chosen as a positive control [19,20].…”
Section: Siderophore Productionmentioning
confidence: 99%
“…Change of blue color of the medium surrounding the bacterial growth to fluorescent yellow indicated the production of siderophore. Bacillus subtilis was chosen as a positive control [19,20].…”
Section: Siderophore Productionmentioning
confidence: 99%
“…Soil microbes expressing a significant level of acid phosphatases/phytases include strains from the genus Rhizobium (Abd-Alla 1994), Enterobacter, Serratia, Citrobacter, Proteus, Klebsiella (Thaller et al 1995), Pseudomonas (Gügi et al 1991;Richardson et al 2001b;Ryu et al 2005), Bacillus (Skrary and Cameron 1998), as well as Sporotrichum thermophile (Singh and Satyanarayana 2010), Emericella rugulosa Tarafdar 2003, 2007b), Discosia sp. FIHB 571 (Rahi et al 2009) and some other fungi.…”
Section: Role Of Microbes In Phosphate Acquisitionmentioning
confidence: 99%
“…Phytase activity derived from soil microorganisms such as Sporotrichum thermophile (Singh and Satyanarayana 2010), Discosia sp. FIHB 571 (Rahi et al 2009), Pseudomonas sp. (Richardson et al 2001b) and Bacillus amyloliquefaciens (Idriss et al 2002) has been shown to contribute to plant growth promotion.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of AM in plant growth and nutrition has been reported elsewhere by several researchers (Bianciotto and Bonfante 2002;Wu et al 2005;Gosling et al 2006;Vyas et al 2007;Rahi et al 2009), and they considered that AM facilitate mobilisation and uptake of those minerals or compounds to the plants which are less soluble and have low mobility (Baslam et al 2011a;Alizadeh 2012;Baslam and Goicoechea 2012;Baslam et al 2013a, b, c). Although most of the work has been done on P (phosphorus) and N (nitrogen), AM also mobilises other minerals such as Zn, Mg, S, Ca, K, etc.…”
Section: Role Of Am In Plant Nutrient Uptake and Growthmentioning
confidence: 81%